Development of Paint-Type Dye-Sensitized Solar Cell Using Carbon Nanotube Paint. (1st April 2019) - Matsunaga, Yuki; Oya, Takahide
Abstract : This paper proposes paint-type dye-sensitized solar cells (DSCs). DSCs, one type of solar cell, generally consist of a dye-attached semiconducting electrode, a metallic electrode, and an electrolyte. The DSC generates power through the excitation of the electrons in the dyes and the oxidation-reduction reaction between the dyes and the electrolyte. For our paint-type DSC, we made two electrodes by painting two types of paint on substrates. We used carbon nanotubes (CNTs) as the paint material because they have both semiconducting and metallic properties. This enabled us to prepare semiconducting and metallic electrodes easily by simply painting with the CNT paint. As a result of testing, we determined that our DSCs were capable of power generation. Our paint-type DSCs have the potential to provide power as a unique and useful device for daily life in the near future.